Experimental evaluation of mechanical heart support system based on viscous friction disc pump - A. M. Chernyavskiy; T. M. Ruzmatov; A. V. Fomichev; A. E. Medvedev; Yu. M. Prikhodko; V. M. Fomin; V. P. Fomichev; K. A. Lomanovich; A. M. Karaskov (Вестник трансплантологии и искусственных органов)
Aim. Experimental evaluation of the viscous friction disk pump efficiency, studying the relationship between inter-disk clearance and sizes of input and output ports and pump performance parameters.Materials and methods. To assess the characteristics and to optimize the disk friction pump design the pump model and experimental stand were created. Pump dimensions were set on the basis of medical and biological requirements for mechanical heart support systems and with due consideration of the experimental studies of our colleagues from Pennsylvania. Flow volume of the working fluid was measured by float rotameter Krohne VA-40 with measurement error of not more than 1%. The pressure values in the hydrodynamic circuit were measured using a monitor manufactured by Biosoft-M. Expansion device allowed changing the flow resistance of the system simulating the total peripheral resistance of the circulatory system.Results. Linear direct correlation between the pump performance and the pressure drop of liquid being created at the inlet and outlet of the pump was obtained. The required flow rate (5–7 l/min) and pressure (90–100 mmHg) were reached when the rotor speed was in the range of 2500–3000 rev/min. It has been shown that the increase of the inlet diameter to 15 mm has not resulted in a significant increase in the pump performance, and that the highest efficiency values can be obtained for the magnitude of inter-disk gap of 0.4–0.5 mm.Conclusion. Designed and manufactured experimental disc pump model for pumping fluid has showed the fundamental possibility to use this model as a system for mechanical support of the heart.